Radial Differentiation of Pump and Signal Intensities in Trapezoidal index EDFA for LP11 mode in Kerr nonlinear state - Ray, Biplab Kumar; Majumdar, Angshuman; Gangopadhyay, Sankar (Journal of Electronics and Informatics, 2022)
An Erbium-Doped Fiber Amplifier (EDFA) is an in-line component in modern all –optical telecommunication infrastructure. Different parametric characteristics of an EDFA express the suitability and excellency of performance in its real field application. Intensities of pump and signal vary with distance from the core-axis along the radius of the fiber which is one of the significant characteristics of an EDFA. Change of behavior of pump and signal intensities along the radius of the fiber in an erbium-doped dual-mode trapezoidal index fiber made amplifier due to Kerr nonlinearity phenomenon originating from launching and transmission of intense light from LASER beam inside the amplifier for the LP_11 mode has been exercised in this case. In the present case, some trapezoidal-index fibers of different normalised frequencies have been opted. This exercise is an implementation of the reliable and easy mathematical instrument, the Chebyshev technique. Results derived in this exercise exhibit a fantastic similarity with those derived by the rigorous finite element method. This study with implementation of such a reliable and easy technique may help the interested optical engineers.
Keywords: EDFA; trapezoidal-index fiber; dual-mode; intensity of〖 LP〗_11mode; Kerr nonlinear state; Chebyshev technique